Optical resolver and method of use - Saleh, Tanveer; Saiful, Islam; Latief, Marsad; Mohd Razib, Mohd Asyraf (2018)
The invention relates to a rotary system in general. More particularly, the invention relates to an optical resolver capable of measuring rotation angle of a rotating member for determining speed, displacement and direction.